Association Between COVID-19 Risk Perceptions and Economic Expectations During the Pandemic in South Korea - Jun Hyung Kim; Jin-Hwan Kim; Jong Jae Lee; Deok Hyun Jang; Won Mo Jang (SAGE Open)
Risk perceptions of the COVID-19 pandemic changed economic expectations and shaped individuals’ consumption and investment choices, thereby worsening its economic and social damage. This study investigated the associations between COVID-19 risk perceptions and economic expectations using a South Korean dataset collected during the pandemic. The results of a logistic regression conducted on 1,001 participants revealed that greater pandemic risk perceptions were significantly associated with negative economic expectations at both the national and the household levels. Affective risk perception had a large and significant negative association with all four types of economic expectations, whereas cognitive risk perception had a significant negative association only with households’ economic expectations. The association was greater for the perception that the economy would “get better” than for “get worse” or “remain the same,” indicating COVID-19 may have reduced individuals’ optimistic economic expectations. COVID-19’s economic damage may last beyond the pandemic, as individuals adjust their economic expectations.